Kegiatan Toleransi Beragama Mahasiswa KKN di Desa Naitimu - Maximelianus Manek Amleni; Apolinarius Manek Usboko; Maria Augustin Lopes Amaral (Universitas Pahlawan Tuanku Tambusai, 2023)
Places of worship become places of fellowship where everyone is welcome. However, this is a public space that many people frequently visit. Therefore cleanliness is very important; it must always be clean and pleasant, offering safety and comfort to everyone who visits it. Efforts to clean places of worship were carried out by KKN Unwira students so that people began to care about the cleanliness of places of worship. Until now, church congregations and mosques have not realized the importance of cleanliness in places of worship. The method used in this community service activity is through surveys, implementation, and evaluation. Cleaning places of worship is carried out regularly for a month by KKN students so that the congregation can feel comfortable when worshiping.